Figurative Framing: Shaping Public Discourse Through Metaphor, Hyperbole, and Irony. Issue 4 (4th April 2016) - Burgers, Christian; Konijn, Elly A.; Steen, Gerard J.
Abstract: Framing is an important concept in communication, yet many framing studies set out to develop frames relevant to only one issue. We expand framing theory by introducing figurative framing. We posit that figurative language types like metaphor, hyperbole and irony are important in shaping public discourse, because these figures contain important linguistic and conceptual content about the issue under discussion. We first explicate the role of each individual figure (metaphor, hyperbole, and irony) in the framing of important societal issues. Then, we focus on complex figurative frames (combinations of metaphor, hyperbole, and/or irony). The article concludes with a research agenda, connecting figurative framing to the four key processes in framing research (frame building, frame setting, individual-level effects, and feedback loop).